2011
DOI: 10.1080/14616734.2011.553999
|View full text |Cite
|
Sign up to set email alerts
|

Sleep architecture and sleep-related mentation in securely and insecurely attached people

Abstract: Based on REM sleep's brain activation patterns and its participation in consolidation of emotional memories, we tested the hypothesis that measures of REM sleep architecture and REM sleeprelated mentation would be associated with attachment orientation. After a habituation night in a sleep lab, a convenience sample of 64 healthy volunteers were awakened 10 minutes into a REM sleep episode and 10 minutes into a control NREM sleep episode in counterbalanced order, then asked to report a dream and to rate themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 43 publications
(41 reference statements)
4
26
1
1
Order By: Relevance
“…Given inconsistencies in the assessment of attachment, the current findings cannot be directly compared with those of previous studies utilizing self-reports of attachment anxiety and avoidance. Nonetheless, the current findings are clearly consistent with the majority of past studies that have found one or more forms of attachment insecurity to be associated with selfreports of sleep problems [24][25][26]28,29,32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Given inconsistencies in the assessment of attachment, the current findings cannot be directly compared with those of previous studies utilizing self-reports of attachment anxiety and avoidance. Nonetheless, the current findings are clearly consistent with the majority of past studies that have found one or more forms of attachment insecurity to be associated with selfreports of sleep problems [24][25][26]28,29,32].…”
Section: Discussionsupporting
confidence: 92%
“…Three studies examined clinical populations, including women with recurrent major depression [30], military veterans with posttraumatic stress disorder symptoms and sleep disturbances [31], and breast cancer survivors [32]. In general, these studies found support for an association between attachment insecurity and poorer self-reported sleep quality [24][25][26]28,29,32]. Approximately equal numbers of studies have found attachment avoidance [24,26,28,29,32] and attachment anxiety [24][25][26]32] to be related to self-reported sleep problems, with three obtaining significant findings regarding both forms of insecurity [24,26,32].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dentre essas, a privação do sono é a mais comum entre adultos jovens, e as mudanças do O presente estudo demonstrou que a presença de sonolên-cia diurna em estudantes de Medicina está associada a menores escores gerais de habilidades sociais. Essa associação entre distúrbios do sono e habilidades emocionais tem sido apontada por outros estudos 31,32 . A presença de sonolência excessiva associa-se a maior dificuldade de leitura de ambiente, ou seja, menor capacidade de identificar as variáveis do ambiente para reagir de acordo com a situação.…”
unclassified
“…Their mutual relationship is not fully clarified but a number of studies point to a coordinating, and hence primary, role of the hippocampal theta (Hasselmo 2005;Sirota et al 2008). 24 This initial proposal has now been corroborated in a number of studies (McNamara et al 2001;McNamara et al 2007;McNamara et al 2011). autistic children have a much smaller REM sleep percentage of total sleep time than healthy controls. Likewise, other sleep disorders common to autistic children also seem to be related to perturbations of REM sleep (Devnani and Hedge 2015).…”
Section: Rem Sleep Mental Rehearsal and Attachmentmentioning
confidence: 83%